'I think youtube's turning me into a flat earther': Social media's role in ex-conspiracy theorists entering and exiting anti-scientific communities. - Chanais Matthias; Yael Benn; Ben Harkin (PLoS ONE)
Conspiracy beliefs erode trust in science and lead to negative effects on public health and other science-related behaviours and political discourse. Despite extensive research on conspiratorial thinking, the literature lacks a comprehensive exploration of individuals' experiences as they enter (and exit) conspiracy communities, presenting a notable research gap. Therefore, the present study adopts an interpretivist framework by interviewing four ex-conspiracy theorists, delving into what drew them into conspiratorial thinking, the catalysts for their exit from these online communities (e.g., Flat Earth, distrust of science and medicine), and the obstacles they faced in disengaging from these communities. Reflective Thematic Analysis identified four main themes with eight associated subthemes. The experiences of ex-conspiracy theorists revealed a profound personal dimension for them entering the conspiracy echo chamber (Theme 1), such as feelings of loneliness and the impact of significant life events. Scientific illiteracy and a general misunderstanding of the scientific process (Theme 2), further contributed to their adoption of more entrenched conspiratorial thinking. The (online) conspiracy community, with its powerful and dynamic nature, had impacted the experiences of members (Theme 3), providing a sense of identity, reinforcing community doctrine, and creating a social and personal barrier to leaving the community. Leaving the community proved a challenging process (Theme 4), with participants identifying a conflict between their personal experiences and the community's doctrine as a key reason for their departure. We contextualize these findings within prior research and propose potential interventions for individuals susceptible to scientific misinformation, utilizing the principles of nudge theory for behaviour change and mindfulness-based therapies.